Islamic-Based Group Counseling towards the Realization of a Sakinah Family: Mentoring for Mothers in the Family Empowerment and Welfare Program of Puti Bungsu, Nagari Tabek - Ira Oktarini; Yanti Elvita (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2026)
The family serves as a fundamental pillar in building a harmonious and prosperous society. However, modern challenges such as economic pressures, permissive social environments, and a lack of religious understanding often hinder the creation of a sakinah family (a family characterized by tranquility, love, and mercy). This community service initiative aims to enhance the understanding and skills of the